PENGARUH CURRENT RATIO, RETURN ON ASSET, DAN STRUKTUR AKTIVA TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL PEMODERASI - Karlina, Berlian; Mulya, Ali Sandy; Said, Said (Economic Faculty, Attahiriyah Islamic University, 2019)
This study aim to analyzing the effect of current ratio, return on assets, and asset structure on firm value with dividend policy as a moderating variable. The multiple linear regression and analysis tools using SPSS Version 20 and Microsoft Excel 2016 was used to test the hypothesis. The data used are secondary data in the form of complete financial statements during the study period. The results showed that the current ratio, return on assets, has an influence on firm value, and only the structure of assets has no effect on firm value. While the dividend policy as a moderating variable influence the current ratio and asset structure to firm value